Nuclear Receptors and Clearance of Apoptotic Cells: Stimulating the Macrophage’s Appetite - A-Gonzalez, Noelia; Hidalgo, Andrés (Frontiers in Immunology, 2014)
Clearance of apoptotic cells by macrophages occurs as a coordinated process to ensure tissue homeostasis. Macrophages play a dual role in this process; first, a rapid and efficient phagocytosis of the dying cells is needed to eliminate uncleared corpses that can promote inflammation. Second, after engulfment, macrophages exhibit an anti-inflammatory phenotype, to avoid unwanted immune reactions against cell components. Several nuclear receptors, including LXR and PPAR, have been linked to these two important features of macrophages during apoptotic cell clearance. This review outlines the emerging implications of nuclear receptors in the response of macrophages to cell clearance. These include activation of genes implicated in metabolism, to process the additional cellular content provided by the engulfed cells, as well as inflammatory genes, to maintain apoptotic cell clearance as an “immunologically silent” process. Remarkably, genes encoding receptors for the so-called “eat me” signals are also regulated by activated nuclear receptors after phagocytosis of apoptotic cells, thus enhancing the efficiency of macrophages to clear dead cells.